Can atrioventricular node ablation be safely performed in patients with permanent His bundle pacing? Data from a multicentric registry. (25th November 2020) - Chaumont, C; Auquier, N; Mirolo, A; Popescu, E; Milhem, A; Al Arnaout, A; Savoure, A; Godin, B; Eltchaninoff, H; Anselme, F
Abstract: Introduction: Ventricular rate control is essential in the management of atrial fibrillation. Atrioventricular node ablation (AVNA) and ventricular pacing can be an effective option when pharmacological rate control is insufficient. However, right ventricular pacing (RVP) induces ventricular desynchronization in patients with normal QRS and increases the risk of heart failure on long term. His bundle pacing (HBP) is a physiological alternative to RVP. Observational studies have demonstrated the feasibility of HBP but there is still very limited data about the feasibility of AVNA after HBP. Purpose: To evaluate feasibility and safety of HBP followed by AVNA in patients with non-controlled atrial arrhythmia. Methods: We included in three hospitals between september 2017 and december 2019 all patients who underwent AVNA for non-controlled atrial arrhythmia after permanent His bundle pacing. No back-up right ventricular lead was implanted. AVNA procedures were performed with 8 mm-tip ablation catheter. Acute HBP threshold increase during AVNA was defined as a threshold elevation >1V. His bundle capture (HBC) thresholds were recorded at 3 months follow-up. Results: AVNA after HBP lead implantation was performed in 45 patients. HBP and AVNA were performed simultaneously during the same procedure in 10. AVNA was successful in 32 of 45 patients (71%). Modulation of the AV node conduction was obtained in 7 patients (16%). The mean procedure duration was 42±24min, and mean fluoroscopy duration was 6.4±8min. A mean number of 7.7±9.9 RF applications (347±483 sec) were delivered to obtain complete / incomplete AV block. Acute HBC threshold increase occurred in 8 patients (18%) with return to baseline value at day 1 in 5 patients. There was no lead dislodgment during the AVNA procedures. Mean HBC threshold at implant was 1.26±0.69V@0.5ms and slightly increased at 3 months follow-up (1.34±0.86V@0.5ms). AV node re-conduction was observed in 5 patients (16% of the successful procedures) with a second successful ablation procedure in 4 patients. No ventricular lead revision was required during the follow-up period. The baseline native QRS duration was 102±21 ms and the paced QRS duration was 107±18 ms. Conclusion: AVNA combined with HBP for non-controlled atrial arrhythmia is feasible and does not compromise HBC but seems technically difficult with significant AV nodal re-conduction rate. The presence of a back-up right ventricular lead could have changed our results and therefore would require further evaluation. Funding Acknowledgement: Type of funding source: None